Why women count video clip collection. [Disc 2], Western Europe, Central Europe, Commonwealth of Independent States and Asia - Films for the Humanities & Sciences (Firm) (Princeton, N.J. : Films for the Humanities & Sciences, 2008)
Filmed in 14 countries, this collection of video segments spotlights Jasmila Zbanic, Ute Bock, Francoise Gaspard, and 13 other women who are making a difference in Europe and Asia.
[1]. Western Europe. Spain : hitting the bottom ; France : Paris parity ; Italy : Rosa ; Austria : Mama Bock -- [2]. Central Europe. Czech Republic : choosing Life ; Bosnia and Herzegovina : speaking out ; Kosovo : women of Krusha ; Macedonia : Biljana from Alcatraz ; Latvia : born to be in business ; Lithuania : girls don't cry -- [3]. CIS and Asia. Ukraine : being positive ; Kazakhstan : hope for life ; Uzbekistan : seeking happiness ; China : Geng Liufen's new world ; Japan : a ticket to Japan.
Title from disc surface.
DVD-R; this disc is a recorded DVD and may not play on all DVD players or drives.
Closed-captioned.
Keywords: Women -- Asia -- Social conditions; Women -- Europe, Central -- Social conditions; Women -- Europe, Western -- Social conditions; Women -- Former Soviet republics -- Social conditions; Women's rights -- Asia; Women's rights -- Europe, Central; Women's rights -- Europe, Western; Women's rights -- Former Soviet republics; Documentary films; Nonfiction films; Video recordings for the hearing impaired